Performance evaluation of asphalt binders incorporating surface-modified diatomite and bio-oil: A value-added utilization of natural resource - Youyun Li; Tao He; Jianliang Tang (Case Studies in Construction Materials, 2024)
To study the effect of surface-modified diatomite (SMD) on bio-asphalt performance, the asphalt binders incorporating SMD and bio-oil (SMDB) was prepared with different dosages. The high-temperature characteristics of SMDB were assessed by consistency test, viscosity test, and dynamic shear rheometer (DSR). Meanwhile, the low-temperature characteristics of SMDB were evaluated by bending beam rheometer (BBR) and ductility test. The compatibility of SMDB was assessed by a storage stability test and a Fluorescence microscope (FM). The adhesion and chemical composition of SMDB were analyzed using the sessile drop method and Fourier transform infrared (FTIR) spectroscopy, respectively. Finally, the moisture stability and high-temperature properties of the SMDB mixture were studied using the tensile strength ratio (TSR) test and wheel track test, respectively. The preliminary results of this work show that the addition of SMD increases the viscosity, softening point, fatigue index, and rutting factor of asphalt and reduces the penetration. It is found that SMD improves the anti-aging performance, adhesion performance, and high-temperature stability of SMDB. Although SMD has a negative effect on the low-temperature properties and fatigue resistance of asphalt, the characteristics of SMDB at low temperatures are still superior to those of virgin asphalt. SMD at low content had little effect on the fatigue resistance of the bio-asphalt. Moreover, it is found that SMD is better than the original diatomite in enhancing bio-asphalt properties more significantly. In addition, the blending among SMD, asphalt matrix, and bio-oil is the physical modification, and the mixture has excellent storage stability. Finally, the mixture property testing results indicate that SMD improves the rutting and moisture resistance of the SMDB mixture.